PENDIDIKAN MORAL AISYAH R.A DALAM BUKU SULAIMAN AN-NADAWI - Siswanto Siswanto; Nirna Lensi; Ifnaldi Nurmal; Eli Susanti (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2021)
The purpose of this study is to explain how the concept of moral education contained in Sulaiman An-Nadawi's book. This research is motivated by the need for a solution to overcome the negative impact on the moral field, which currently requires a real person as an example in implementing a moral life. This research is a library research (library research). the main data source is Sulaiman An-Nadawi's book about Aisyah as a Muslim Ummah. The type of data collection in this research is through reading, describing, and reviewing the contents of the book that is being researched or used as a research source, then the type of approach used is content analysis. Sulaiman An-Nadawiini include: (1) The concept of moral education related to God (2) The concept of moral education related to oneself. (3) The concept of moral education related to fellow human beings.